Improvement in aerobic capacity during cardiac rehabilitation in coronary artery disease patients: Is there a role for autonomic adaptations?. (March 2017) - Lazzeroni, Davide; Castiglioni, Paolo; Bini, Matteo; Faini, Andrea; Camaiora, Umberto; Ugolotti, Pietro Tito; Centorbi, Claudio Stefano; Brambilla, Lorenzo; Brambilla, Valerio; Piepoli, Massimo Francesco; Coruzzi, Paolo
Background: It has been previously shown in patients with heart failure that exercise-based rehabilitation programmes may improve functional capacity and autonomic response. The aim of this study was to investigate this issue further by evaluating whether an association exists between autonomic adaptations and improvements of aerobic capacity in a general population of coronary artery disease patients undergoing cardiac rehabilitation. Methods: Ninety consecutive patients (age 60 ± 11 years) attended a rehabilitation programme of moderate continuous training (25 ± 8 sessions, 2–3 sessions/week). Functional capacity expressed as oxygen uptake (peak VO2 ) and autonomic function expressed as chronotropic response and heart rate recovery were evaluated by cardiopulmonary exercise tests before and after the rehabilitation programme. According to the expected mean increase in functional capacity, coronary artery disease patients were divided into two groups: those who improved peak VO2 by more than 2.6 ml/kg/min (R group) and those who did not (NR group). Effects of the rehabilitation programme were compared in R and NR groups. Results: The number and intensity of exercise sessions did not differ between R ( N  = 39) and NR ( N  = 51) groups. However, only R patients improved chronotropic response (R: from 45.1 ± 16.9% to 72.7 ± 34.1%, P  < 0.01; NR: from 49.3 ± 18.6% to 48.2 ± 36.5%, P  = NS) and heart rate recovery (R: from 16.9 ± 7.0 bpm to 21.0 ± 8.7 bpm, P  < 0.01; NR: from 15.2 ± 9.9 bpm to 15.8 ± 8.5 bpm, P  = NS). After training both chronotropic response and heart rate recovery were significantly higher in R than NR patients. Conclusions: The improvement in aerobic capacity of coronary artery disease patients following exercise-based cardiac rehabilitation programmes is associated with positive adaptations of autonomic function.